2017
DOI: 10.1177/2167702616672038
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Weaknesses in the Intellectual Profile of Different Subtypes of Specific Learning Disorder

Abstract: The consideration of intelligence has always been crucial for the diagnosis of specific learning disorders (SLDs). In particular, the hypothesis of a discrepancy between normal to high general intellectual abilities and poor academic achievement has traditionally been stressed (Mercer, Jordan, Allsopp, & Mercer, 1996). However, the traditional view of SLD has been criticized (e.g., Siegel, 1988). First of all, the dimensional distribution of academic and intellectual performances (i.e., a continuum of severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 28 publications
7
63
1
4
Order By: Relevance
“…Our results indicate that children with DD can be disentangled into two main clusters. The first is characterized by children with higher IQs, with a PRI generally higher compared with the VCI, consistent with previous observations (Toffalini, Giofrè, & Cornoldi, ). This cluster is also characterized by a striking dissociation of performance—a visual processing weakness coupled with intact phonological processing.…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate that children with DD can be disentangled into two main clusters. The first is characterized by children with higher IQs, with a PRI generally higher compared with the VCI, consistent with previous observations (Toffalini, Giofrè, & Cornoldi, ). This cluster is also characterized by a striking dissociation of performance—a visual processing weakness coupled with intact phonological processing.…”
Section: Discussionsupporting
confidence: 90%
“…First, in agreement with previous studies, we found that children with DD failed in a WM task in which they were asked not only to recall, but also to manipulate and process previously presented information Passolunghi & Siegel, 2001;Schuchardt, et al, 2008;Swanson & Sachse-Lee, 2001;Szűcs, 2016). It is also well known that the general cognitive profile of children with specific learning disorders shows impairment in WM and processing speed indexes (Giofrè & Cornoldi, 2015;Toffalini, et al 2017). Additionally, to better understand the role of WM impairments in DD and MA groups, we compared their performances with the combined group (i.e., MA-DD).…”
Section: Discussionsupporting
confidence: 77%
“…Calhoun & Mayes ; Toffalini et al . ), with weaknesses especially in working memory and processing, as also suggested by previous research on intellectual disability (e.g. Kail ; Henry et al .…”
supporting
confidence: 72%